2022
DOI: 10.1111/jipb.13236
|View full text |Cite
|
Sign up to set email alerts
|

MdbHLH3 modulates apple soluble sugar content by activating phosphofructokinase gene expression

Abstract: Sugars are involved in plant growth, fruit quality, and signaling perception. Therefore, understanding the mechanisms involved in soluble sugar accumulation is essential to understand fruit development.Here, we report that MdPFPβ, a pyrophosphatedependent phosphofructokinase gene, regulates soluble sugar accumulation by enhancing the photosynthetic performance and sugar-metabolizing enzyme activities in apple (Malus domestica Borkh.). Biochemical analysis revealed that a basic helix-loop-helix (bHLH) transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…The IAA–LEUCINE RESISTANT 3 ( Rh ILR3; Rh bHLH105)–LESION SIMULATING DISEASE ONE LIKE 1 ( Rh LOL1) module regulates petal abscission by directly binding to the RhIAA4-1 promoter in roses [ 53 ]. Additionally, MdbHLH3 regulates sugar metabolism in apples by binding directly to the promoter of PYROPHOSPHATE-DEPENDENT PHOSPHOFRUCTOKINASE ( MdPFPβ ) to activate its expression, thereby increasing fructose-6-phosphate and sucrose concentrations [ 54 ]. In rice, OsbHLH067, OsbHLH068, and OsbHLH069 redundantly regulate inflorescence AM formation [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The IAA–LEUCINE RESISTANT 3 ( Rh ILR3; Rh bHLH105)–LESION SIMULATING DISEASE ONE LIKE 1 ( Rh LOL1) module regulates petal abscission by directly binding to the RhIAA4-1 promoter in roses [ 53 ]. Additionally, MdbHLH3 regulates sugar metabolism in apples by binding directly to the promoter of PYROPHOSPHATE-DEPENDENT PHOSPHOFRUCTOKINASE ( MdPFPβ ) to activate its expression, thereby increasing fructose-6-phosphate and sucrose concentrations [ 54 ]. In rice, OsbHLH067, OsbHLH068, and OsbHLH069 redundantly regulate inflorescence AM formation [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that PpS6PDH is a reversible enzyme, its role in fruit ripening requires further investigation. In apples, activation of a pyrophosphate-dependent phosphofructokinase gene can promote soluble sugar accumulation ( Yu et al., 2022 ). In sweet pear cultivars evaluated in the present study, the gene encoding 6-phosphofructokinase 7 was upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…A phosphofructokinase: pyrophosphate-fructose 6-phosphate 1-phosphotransferase (ClPFP1, Cla97C11G225220) was found. Previous study reported that PFP activity showed a positive correlation with sucrose content in apple fruit (Yu et al, 2022). We therefore hypothesized that ClSnRK2.3 may directly phosphorylate ClPFP1 to regulate watermelon fruit sugar accumulation.…”
Section: Clsnrk23 Phosphorylated Phosphofructokinase Clpfp1 the Ga Bi...mentioning
confidence: 91%